2010
DOI: 10.1111/j.1365-2958.2009.07011.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of configuration and coupling in autoregulatory gene circuits

Abstract: SummaryAutoregulatory gene circuits can be physically encoded within the genome in a number of different configurations. By physical encoding, we mean the orientation and relative proximity of the genes within the circuit. In this work, we quantified the behaviour of an inducible, negatively autoregulated gene circuit arranged in different transcriptional configurations using the tetRA circuit from Tn10 as our basis. Mathematical modelling predicted that circuits arranged in configurations where the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 43 publications
(52 reference statements)
0
26
0
Order By: Relevance
“…Based on these results, the authors speculated that natural circuits could evolve using a similar approach - rather than evolve a circuit with a single regulator requiring precise biochemical properties, a more robust and facile solution may be obtained by simply linking together multiple regulators that alone lack the requisite properties. Similarly, others have shown that by changing the regulatory architecture of a circuit one can affect is behavior without commensurate changes in the underlying proteins [54], [55], [56]. We hypothesize that a similar process may have occurred with the SPI1 gene circuit.…”
Section: Discussionmentioning
confidence: 57%
“…Based on these results, the authors speculated that natural circuits could evolve using a similar approach - rather than evolve a circuit with a single regulator requiring precise biochemical properties, a more robust and facile solution may be obtained by simply linking together multiple regulators that alone lack the requisite properties. Similarly, others have shown that by changing the regulatory architecture of a circuit one can affect is behavior without commensurate changes in the underlying proteins [54], [55], [56]. We hypothesize that a similar process may have occurred with the SPI1 gene circuit.…”
Section: Discussionmentioning
confidence: 57%
“…S5A to C in the supplemental material). However, we cannot directly compare these experiments with one another, as the responses to yeast extract and aTc are not orthogonal: as yeast extract concentrations increase, expression from the tetracycline-inducible P tetA promoter (23) decreases, for unknown reasons (see Fig. S5D in the supplemental material).…”
Section: Resultsmentioning
confidence: 99%
“…The data were normalized relative to those from the experiments using 0.2% yeast extract. (D) P tetA promoter activity as a function of aTc and yeast extract measured using mCherry transcriptional fusion in a strain where the repressor TetR is produced independently from the P tetR promoter (23). Data are averages from three independent repeats, and error bars indicate standard deviations.…”
Section: Supplemental Materialsmentioning
confidence: 99%
“…Of these hits, ten had an additional frank structural change to a divergent expression pattern originating between lacI and lacZ characters (e.g. in E. cloacae ), likely increasing system sensitivity to lacI repression in these cases [15]. Surprisingly, in other instances, extended window searching revealed the only proximal structural change to be a missing lacA gene.…”
Section: Resultsmentioning
confidence: 99%